Developing Cover Song-Based Multimedia to Support Pancasila Education in Primary Schools - Misdiantoro, Adill Fulki Amalia; Uswatun Hasanah (The Elementary Journal, 2025)
This research is a development research that aims to analyze, design, develop, implement and evaluate Cover Song media. The results showed the need for interactive media and help understanding Pancasila education material for grade III SD / MI. Selection of children's songs that students already know, making lyrics that are easy to understand, different video concepts, and devices as well as Canva and CapCut applications to support the development of Cover Song media. The gadget is used as a sound recording device, Canva and CapCut applications for video editing. Validation by material experts obtained a percentage of 100% including very valid criteria. The results of validation by learning video experts obtained a percentage of 96.48% including very valid criteria. The results of the trial to the teacher obtained a percentage of 100% (very good), the small group obtained a percentage of 92.85% (very good), the results of the large group trial 97.71% (very good), and the results of the field trial 97.80% (very good). Based on the results of validation and research trials, the media developed is feasible to be used as learning media. The results of the trial show that there is no need for revision, Cover Song media get very good validation results and trials with very good response results, so it can be concluded that Cover Song media can be used as learning media to answer existing needs in the learning process.